2014
DOI: 10.2351/1.4898835
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of TiAl6V4 lattice structures manufactured by selective laser melting in quasistatic and dynamic compression tests

Abstract: This paper focusses on the investigation of the mechanical properties of lattice structures manufactured by selective laser melting using contour-hatch scan strategy. The motivation for this research is the systematic investigation of the elastic and plastic deformation of TiAl6V4 at different strain rates. To investigate the influence of the strain rate on the mechanical response (e.g., energy absorption) of TiAl6V4 structures, compression tests on TiAl6V4-lattice structures with different strain rates are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 16 publications
3
36
0
1
Order By: Relevance
“…[18,19] BCC topological structure is introduced, since its extensively experimentally and theoretically examined. [37] More importantly, the CoCrFeNiAl 0.3 HEA thin film coating fabricated via radio frequency (RF) sputtering methodology has been developed and applied in nanolattice structures for the first time. Combining the merits of HEA and polymer nanolattice structures, the presented hybrid nanolattices exhibit superior compressive specific strength of 0.032 MPa kg À1 m 3 with density below 1000 kg m À3 , while still own an admirable compressive ability as compared to those made by pure metal/alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] BCC topological structure is introduced, since its extensively experimentally and theoretically examined. [37] More importantly, the CoCrFeNiAl 0.3 HEA thin film coating fabricated via radio frequency (RF) sputtering methodology has been developed and applied in nanolattice structures for the first time. Combining the merits of HEA and polymer nanolattice structures, the presented hybrid nanolattices exhibit superior compressive specific strength of 0.032 MPa kg À1 m 3 with density below 1000 kg m À3 , while still own an admirable compressive ability as compared to those made by pure metal/alloys.…”
Section: Introductionmentioning
confidence: 99%
“…As this SLM printed tube can experience the two modes during the crushing process, both the advantages of the two modes can be taken in one structure. The tube is completely compacted in Image (14), the final crush morphology of the experimental and numerical results are shown in Images (15) and (16) in Fig. 10.…”
Section: Z Yang Et Almentioning
confidence: 99%
“…When the SLM printed structure bears axial loading, the brittle character of the material tends to induce fracture of the structure. For example, the SLM printed TiAl6V4 lattice structure fractures when the macroscopic strain reaches 20% due to the low ductility (~10%) of the material [14]. For the buckling mode of the SLM printed thinwalled tube, the plastic hinges may not bend into a complete fold before it fractures because of the material brittleness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 For implant fixation, a big draw of AM technology is the ability to create porous structures that bone can grow into, allowing improvement in long-term fixation; consequently porous structures have been extensively researched. [22][23][24][25][26][27][28][29][30][31][32] Recent research has also suggested that AM fixation features could improve the initial stability of implants. 14,15 This area has been much less researched but is of equal importance as initial implant stability is a prerequisite for long-term fixation.…”
mentioning
confidence: 99%